Historical and current juridical aspects of cooperation between international scheduled liner shipping organisations: a South African perspective - De Vos, Andrew (Shipping Law Unit, 2025)
Shipping companies involved in the scheduled liner shipping trade are essentially concerned with providing a regular ocean transport service to shippers. This service consists of a fixed sailing pattern on a publicised schedule operating on a specific geographic trade route. It is essentially a regular service with voyages tendered to take place on certain dates or at fixed intervals.